Selection of affinity peptides for the purification potential of porcine circovirus type 2 (PCV2) Cap virus-like particles (VLPs). Issue 62 (8th August 2017) - Zheng, Guanmin; Lu, Qingxia; Wang, Fangyu; Jin, Qianyue; Teng, Man; Zhang, Nana; Ren, Tingting; Ding, Peiyang; Zhang, Gaiping
Abstract : In this study, we describe the use of a M13 phage-displayed random peptide library for screening novel peptide motifs that specifically recognize recombinant PCV2 Cap protein for the first time. Abstract : In this study, we describe the use of a M13 phage-displayed random peptide library for screening novel peptide motifs that specifically recognize recombinant PCV2 Cap protein for the first time. The peptide had a sequence of YHDCFSAGFCIG, and the binding affinity was observed in the nanomolar range. In the serum blocking test, the ELISA signal of the peptide was rapidly decreased when the concentration of the PCV2 positive serum was increased.